Specificity and signaling in the Drosophila immune response. - Silverman, N.; Paquette, N.; Aggarwal, K. (Invertebrate survival journal, 2009)
The Drosophila immune response is characterized by the rapid and robust production of a battery of antimicrobial peptides immediately following infection. The genes encoding these antimicrobial peptides are controlled by two NF-?B signaling pathways that respond to microbial infection. The IMD pathway is triggered by DAP-type peptidoglycan, from the cell wall of most Gram-negative and certain Gram-positive bacteria, and activates the NF-?B precursor protein Relish. The Toll pathway, on the other hand, is stimulated by lysine-type peptidoglycan from many Gram-positive bacteria, ? 1,3 glucans from many fungi, as well as by microbial proteases. Toll signaling leads to the activation and nuclear translocation of DIF or Dorsal, two other NF-?B homologs. This review presents our current understanding of the molecular mechanisms involved in microbial recognition and signal transduction in these two innate immune pathways.